STUDENTS’ PERCEPTION ON THE USE OF CODE-MIXING USED BY ENGLISH TEACHERS IN SMA N 1 MINAS - Axyz Aljamil; Erni Erni; M. Syarfi M. Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The term "code-mixing" is used in research of bilingual language acquisition to describe a developmental stage in which children mix vocabulary from different languages. That, the objective of the research is to learn what the students think about using code-mixing in the process of teaching, and based on the final result, it seems that the objective has been achieved. his research was designed using a descriptive- quantitative methodology, They found that code-mixing has positive effects on them. They thought that using code-mixing helped them save time in finding the words to use in a conversation. Students also believed that code-mixing helped them improve their English skill to be better.Keywords: Student’s Perception, Code-Mixing